Comparative Transcriptome and Chloroplast Genome Analyses of Two Related Dipteronia Species - Zhou, Tao; Chen, Chen; Wei, Yue; Chang, Yongxia; Bai, Guoqing; Li, Zhonghu; Kanwal, Nazish; Zhao, Guifang (Frontiers in Plant Science, 2016)
Dipteronia (order Sapindales) is an endangered genus endemic to China and has two living species, D. sinensis and D. dyeriana. The plants are closely related to the genus Acer, which is also classified in the order Sapindales. Evolutionary studies on Dipteronia have been hindered by the paucity of information on their genomes and plastids. Here, we used next generation sequencing to characterize the transcriptomes and complete chloroplast genomes of both Dipteronia species. A comparison of the transcriptomes of both species identified a total of 7,814 orthologs. Estimation of selection pressures using Ka/Ks ratios showed that only 30 of 5,435 orthologous pairs had a ratio significantly greater than 1, i.e., showing positive selection. However, 4,041 orthologs had a Ka/Ks < 0.5 (p < 0.05), suggesting that most genes had likely undergone purifying selection. Based on orthologous unigenes, 314 single copy nuclear genes were identified. Through a combination of de novo and reference guided assembly, plastid genomes were obtained; that of D. sinensis was 157,080 bp and that of D. dyeriana was 157,071 bp. Both plastid genomes encoded 87 protein coding genes, 40 tRNAs, and 8 rRNAs; no significant differences were detected in the size, gene content, and organization of the two plastomes. We used the whole chloroplast genomes to determine the phylogeny of D. sinensis and D. dyeriana and confirmed that the two species were highly divergent. Overall, our study provides comprehensive transcriptomic and chloroplast genomic resources, which will be valuable for future evolutionary studies of Dipteronia.